Efek Suplementasi Vitamin D pada Kadar Hemoglobin Pasien Hemodialisis: Laporan Kasus Berbasis Bukti: Laporan Kasus Berbasis Bukti - Winarsa, Jessica; Sunardi, Diana (PT Kalbe Farma Tbk., 2026)
Introduction: Anemia is a common complication of end-stage chronic kidney disease (CKD), particularly in patients undergoing hemodialysis. Vitamin D, a micronutrient with receptors in various cell types, plays a role in enhancing erythropoiesis by promoting the proliferation of erythroid progenitor cells, reducing proinflammatory cytokines and hepcidin, thereby increasing iron bioavailability for hemoglobin (Hb) synthesis. This study aims to investigate the effect of vitamin D supplementation on Hb levels in chronic hemodialysis patients. Methods: A systematic literature search was conducted across 4 databases: PubMed, ProQuest, Cochrane, and Scopus. Inclusion criteria were studies on adult patients undergoing chronic hemodialysis with anemia and with any vitamin D status, published within the last 5 years, and consisting of systematic reviews and meta-analyses (SR-MA) of randomized controlled trials (RCTs) or RCTs. Critical appraisal was performed using the validity, importance, and applicability (VIA) framework from the Oxford Centre for Evidence-Based Medicine (OCEBM). Results: Two RCTs and one SR-MA were critically appraised. Vitamin D supplementation was found to improve Hb levels in chronic hemodialysis patients, with statistically significant effects observed in longer supplementation durations. Conclusion: Vitamin D supplementation in chronic hemodialysis patients has shown promising results in improving Hb levels. Further research is required to determine the optimal type, dosage,and duration of vitamin D supplementation.